Collaborative Translanguaging Formative Assessment in Mother Tongue-Based Multilingual Education - Leonardo Daquioag Tejano (Universitas PGRI Semarang, 2023)
This research conducted classroom action research in Grade 1 of a Mother Tongue-Based Multilingual Education (MTB-MLE) program, which aims to promote the use of local languages as mediums of instruction in the early years of education. The study found that Ilokano learners tended to use English more often than Ilokano, which highlighted the importance of supporting their cultural identity and heritage through the MTB-MLE program. The Ilokano-Based Translanguaging Approach to Mother Tongue-Based Multilingual Education (IBTA-MTB-MLE) was developed to support instruction, and a formative assessment strategy called Collaborative Translanguaging Formative Assessment (CTFA) was developed to align with the teaching approach. The study aimed to test the effectiveness of CTFA by preparing four lesson sessions where learners work together to think, talk, write, and give feedback using their full range of linguistic repertoire. After the implementation of CTFA, a pre-test and post-test were conducted to determine the achievement of the Ilokano learners in MTB-MLE. The results showed that the majority of the students moved to higher ranges of score after the intervention, with an increase in mean scores from 20.1 to 25.87. The study highlights the benefits of translanguaging in language education and collaboration in assessment.